A Case Study of Students’ Barriers in Passive Voice Sentences - Zahratul Idami; Pratiwi, Diah Ayu Pratiwi (JL3T (Journal of Linguistics, Literature and Language Teaching), 2021)
This study was to find out the errors experienced by students in composing passive voice sentences. It also explained the factors that caused students' barriers in constructing passive voice sentences. This study focused on students' errors and bariers in constructing passive voice sentences in the form of Simple Present Tense, Simple Past Tense, and Present Future Perfect Tense. The research approach used was a qualitative method through a case study. The subject of this research was 12 students in class XII of SMKS Yaspenmas Sei Lepan. Data collection techniques were tests and interviews. The findings of this study were the types of student errors on omission 62.4%, misinformation 10.6%, misordering 27%. As well as the location of the error in the passive voice sentence in the form of Simple Present Tense in the use of to be 75%, past participle 100%, then the use of to be in the Simple Past Tense 95, 83% and past participle 64.6%, then the use of have in Present Future Perfect Tense 36.1%, been 100%, and past participle 33.3%. These errors were due to internal factors and external factors. The internal factors were students’ lack of interest in learning English as well as lack of vocabulary mastery and lack of understanding of grammar. The external factors were lack of parental attention, lack of supporting media in the learning process, inadequate school infrastructures, and the road to school was difficult to pass.